THE COMMUNICATIVE CHARACTERISTICS OF THE MODERN CULTURAL AGE IN THE CONTEXT OF DIGITALIZATION - Antipova, Olha (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The analysis of attributes of modern media landscape has shown the growing significance of the society digitalization. Today, this process extends beyond the purely technological field and serves as a core driver for the transformation of characteristics of the sociocultural space, primarily the communicative interaction. The aim and tasks. This article aims to analyze the communicative characteristics of the modern cultural age in the context of the society digitalization. Research methods. The methodological tools consist of the sociocultural approach, methodological principles of systematicity, and completeness. Research results. The digital model of world perception serves as a background for the deployment of a new communicative strategy, forming an environment for the formation of information culture as a new cultural type. Discussion. Results of the analysis of the communicative characteristics of the modern cultural age in the context of digitalization are adding to the conceptual achievements of theorists in the outlined issue and are jointly aimed at finding the optimal strategy for combating the challenges of globalization. Conclusion. The communicative paradigm of the modern cultural age in the context of digitalization is ambivalent. On the one hand, it provides ample opportunities for the accelerated information exchange, intercultural interaction via Internet platforms, continuous broadcasting and communication online, etc., and on the other hand, under these conditions, the communicative interaction is associated with numerous risks, including information overload, degradation of the critical perception of the information flow, “digital inequality”, imposition of content, use of manipulative technologies, etc. An important factor in addressing these and other problems in creating an optimal model of communicative interaction is the formation of an information culture capable of preserving traditional and developing new values and worldview attitudes able to meet the challenges of globalization.